IMPROVEMENT IN LV END-DIASTOLIC PRESSURE AFTER PRIMARY PCI AND ITS IMPACT ON PATIENTS’ RECOVERY - ABUBAKAR , M; SAQI , MAUR; PERVEZ , S; SIAL , JA; ASHRAF , MW; FAROOQ , M (Biological and Clinical Sciences Research Journal, 2024)
Left ventricular end-diastolic pressure (LVEDP) is a crucial indicator of cardiac function, particularly in patients with acute ST-segment elevation myocardial infarction (STEMI). Primary percutaneous coronary intervention (PCI) is the standard of care for STEMI, but its impact on LVEDP and patient recovery remains to be thoroughly studied. Objective: This study aimed to evaluate the improvement in LVEDP following primary PCI in patients with acute STEMI and to assess its impact on recovery and clinical outcomes. Methods: This prospective study included 100 patients with acute STEMI treated by primary PCI. LVEDP was recorded at four-time points: before PCI, and at one week, one month, and three months post-PCI. Demographic and clinical characteristics were also collected. Statistical analysis was performed to compare LVEDP values at different time intervals using paired t-tests and repeated measures ANOVA to assess significant changes over time. Results: The mean LVEDP significantly decreased from 18 ± 4 mmHg before PCI to 12 ± 3 mmHg at one week, 10 ± 2 mmHg at one month, and 9 ± 2 mmHg at three months post-PCI (p < 0.001). This demonstrated a consistent improvement in left ventricular function and hemodynamic status, suggesting favorable patient recovery post-intervention. Conclusion: Primary PCI significantly reduces LVEDP in patients with acute STEMI, leading to improved cardiac function and patient recovery. Monitoring LVEDP post-PCI can serve as a valuable predictor of patient prognosis and long-term outcomes. Further studies are warranted to explore additional therapies that may further enhance recovery and improve the quality of life in STEMI patients.